Evaluation of IGF1/IGFBP3 Molar Ratio as an Effective Tool for Assessing the Safety of Growth Hormone Therapy in Small-for-gestational-age, Growth Hormone-Deficient and Prader-Willi Children - Meriem Gaddas; Laurence Périn; Yves Le Bouc (Galenos Yayincilik, 2019)
Objective:IGF1 concentration is the most widely used parameter for the monitoring and therapeutic adaptation of recombinant human growth hormone (rGH) treatment. However, more than half the variation of the therapeutic response is accounted for by variability in the serum concentrations of IGF1 and IGFBP3. We therefore compared the use of IGF1/IGFBP3 molar ratio with that of IGF1 concentration alone.Methods:We selected 92 children on rGH for this study and assigned them to three groups on the basis of growth deficiency etiology: small for gestational age (SGA), GH deficiency (GHD) and Prader-Willi syndrome (PWS). Plasma IGF1 and IGFBP3 concentrations and their molar ratio were determined.Results:Before rGH treatment, mean IGF1/IGFBP3 molar ratio in the SGA, GHD and PWS groups was 0.14±0.04, 0.07±0.01 and 0.12±0.02, respectively. After the initiation of rGH treatment, these averages were 0.19±0.07, 0.20±0.08 and 0.19±0.09, within the normal range for most children, even at puberty and despite some significant increases in serum IGF1 levels.Conclusion:We consider IGF1/IGFBP3 molar ratio to be a useful additional parameter for assessing therapeutic safety in patients on rGH, and for maintaning the values within the normal range for age and pubertal stage.